Examination of Athletes’ Anxiety, Motivation, Imagination Value in Competitions with Different Severity Level - SALLAYICI, Mustafa; KOLAYİŞ, İpek EROĞLU; KESİLMİŞ, İnci; KESİLMİŞ, Mehmet Melih (Asian Journal of Education and Training, 2018)
The objective of this study was to examine athletes’ anxiety, motivation and imagination value in competitions with different severity level. The research was conducted on swimming athlete in elite level 18 female and 19 male totally 37. To measure the level of imagination, imagine inventory in sports and to measure trait anxiety levels STAI were used. For statistical analyses of parametric data, to see the difference between the groups independent groups t-test and for the non-parametric data Mann Whitney-U analyses were used. The level of significance accepted as p<0.05. National team athletes and athletes that participate in 13th European Short Course Swimming Championships and Turkey National Team Selection, before the day of the event selection and on the morning of the competition the difference between the cognitive anxiety levels, somatic anxiety levels and confidence levels was not statistically significant (p>0.05). Athletes that participate in 13th European Short Course Swimming Championships and Turkish national team athletes before the day of the event selection and on the morning of the competition while cognitive anxiety and self-confidence levels were statistically different (p<0.05), the difference between somatic anxiety levels was not statistically significant (p>0.05). The athletes that selected and non-selected for national team before the day of the event selection and on the morning of the competition the difference between the cognitive anxiety levels, somatic anxiety levels, confidence levels, motivation and imagination levels was not statistically different (p>0.05).